The Application of CHSE in Cook Interpreter Activities at Sibayak International Hotel Berastagi - Zaitun Zaitun; Ngger Putro Cahyo Hutomo (Tourism, Hospitality And Culture Insights Journal, 2021)
The Ministry of Tourism and Creative Economy is currently implementing CHSE-based health protocols (Cleanliness, Health, Safety and Environment Sustainability) on tourism and creative economy efforts, to revive the sector from the downturn caused by the Covid-19 pandemic. The key to successful tourism in order to rebound immediately is the implementation of CHSE-based health protocols well and disciplined in each destination and tourism sector actors. Berastagi city is one of the tourist cities that is a mainstay of tourism in north Sumatra. This is certainly very related to the implementation of the CHSE program from the government, in order to make tourism activities in Berastagi city bounce back. The purpose of this research is to find out how to understand and apply the CHSE program to employees working in the kitchen department at Sibayak International hotel so as to have a positive impact from the application and can increase the trust of guests to stay. This research is descriptive research with data analysis method is qualitative descriptive. The results of the study can be concluded that cooks get a good understanding of the CHSE program that is being implemented by the government as an effort to prevent the transmission of the covid.19 virus, especially in the kitchen area as the place most at risk of becoming a medium of transmission of bacteria and viruses from humans to processed foods. The implementation of CHSE program in Sibayak Berastagi hotel kitchen goes well so it is expected that it will also have a good influence on the level of trust of guests not to worry about visiting and staying at Sibayak Berastagi hotel.